PRODUKSI KARKAS DAN GIBLET ( JANTUNG, HATI & EMPEDAL ) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
ABSTRAK The experiment was conducted to investigate carcass and giblet production (heart, liver and crop) of male and female young squab at different level of protein in the ration. By using a completely randomized design (CRD), fifteen pairs of ready to lay were used and were devided into three different level of protein in the ration (15.0, 17.5 and 200/0 CP)